Interspecific competition shapes bird species' distributions along tropical precipitation gradients - Benjamin G. Freeman; Eliot T. Miller; Matthew Strimas‐Mackey (Ecology Letters, 2024)
The hypothesis that species' ranges are limited by interspecific competition has motivated decades of debate, but a general answer remains elusive. Here we test this hypothesis for lowland tropical birds by examining species' precipitation niche breadths. We focus on precipitation because it—not temperature—is the dominant climate variable that shapes the biota of the lowland tropics. We used 3.6 million fine‐scale citizen science records from eBird to measure species' precipitation niche breadths in 19 different regions across the globe. Consistent with the predictions of the interspecific competition hypothesis, multiple lines of evidence show that species have narrower precipitation niches in regions with more species. This means species inhabit more specialized precipitation niches in species‐rich regions. We predict this niche specialization should make tropical species in high diversity regions disproportionately vulnerable to changes in precipitation regimes; preliminary empirical evidence is consistent with this prediction.